Interleukin 1α-induced NFκB Activation and Chemokine mRNA Stabilization Diverge at IRAK1 - Hartupee, Justin (American Society for Biochemistry and Molecular Biology, 2008)
Interleukin 1α (IL-1α) is capable of driving pro-inflammatory gene expression through both the initiation of transcription and by prolonging the half-life of short-lived mRNAs. Although the signaling events linking the IL-1 receptor to the activation of NFκB and the initiation of transcription have been well characterized, less is known about the signaling events linking to mRNA stabilization. As a model to study the control of mRNA stability we have used the mouse chemokine KC, expression of which requires both NFκB-driven transcription and stabilization of the constitutively unstable mRNA. We have evaluated the role of signaling adaptors known to play a role in IL-1α-driven NFκB activation in the generation of mRNA stability. Surprisingly, although TRAF6 is essential for NFκB activation, it is not required for IL-1α-induced mRNA stabilization. IRAK1, which is recognized to function upstream of TRAF6, is required for both mRNA stabilization and activation of NFκB. Consistent with the previous findings, the TRAF6 interaction sites in IRAK1 are required for NFκB activation but do not play a role in mRNA stabilization. These findings indicate that signals from the IL-1 receptor segregate into at least two separate pathways at the level of IRAK1; one couples through TRAF6 to NFκB activation while a second utilizes a TRAF6-independent pathway that is responsible for mRNA stabilization.